Level of Knowledge About Coronary Artery Disease is Poor Among Bangladeshi Hospitalized Patient Following Acute Coronary Syndrome - Motlabur Rahman, Md.; Sarker, M.A. Sattar; Mahbub, Tania; Khanam, Shahana; Zafrin, Nahida; Azhar, M.A. (Journal of Medicine, 2014)
Back ground: Coronary artery disease (CAD) is a major risk of death worldwide. Level of education about this important health problem is poor in our general population. Aims of this study was to find out simple knowledge about coronary disease, and to find the knowledge about risk factors, symptoms, complications and knowledge about prevention of coronary disease among the hospitalized patient who admitted to SSMS and Mitford Hospital and diagnosed as patients of Acute Coronary Syndrome (ACS). Method: A pre tested questionnaire regarding assessment of level of knowledge about CAD was used to studied of the patients was admitted to SSMC and Mitford Hospital with the diagnosis of acute coronary syndrome during the period April 2009 to October 2009. Result: Our study suggests that there is a lack of awareness among a sampled Bangladeshi population regarding CAD and its modifiable risk factors. We found that the low level of knowledge in the majority of patients, the rural and less educated patients had a lower level of knowledge. Conclusion: Our cardiac patients have poor knowledge regarding their disease; improvement of knowledge is needed through much education to prevent CAD. DOI: http://dx.doi.org/10.3329/jom.v14i2.19639 J Medicine 2013, 14(2): 119-122